Deflation for block eigenvalues of block partitioned matrices with an application to matrix polynomials of commuting matrices - Pereira, E. (2001)
A method for computing a complete set of block eigenvalues for a block partitioned matrix using a generalized form of Wielandt's deflation is presented. An application of this process is given to compute a complete set of solvents of matrix polynomials where the coefficients and the variable are commuting matrices.